Implant Placement in a Patient with Altered Passive Eruption - Dr Aiemeeza RajaliI; Dr Nadiyah Abdullah Zawawi; Dr Nicola De Angelis; Dr Nik Rahayyu Nik Zulkifeli (Elsevier, 2023)
Introduction: The gingival complex plays a vital role in the overall beauty of a person's smile and the altered passive eruption (APE) is one cause that can make the clinical crown of teeth seems short. Case Description: A 30-year-old female patient with a history of diabetes mellitus was presented to the UiTM Specialist Clinic with the chief concern of a missing tooth and the unsatisfactory appearance of her smile. Clinical examination revealed a missing central incisor and several caries teeth with poor oral hygiene. Periodontal variables were recorded before surgery and anatomical variables were measured clinically and with CBCTs. The present case report aims to describe a multidisciplinary treatment involving the phase of the periodontal surgical sequence of aesthetic crown lengthening for the treatment of APE and simultaneous implant placement. The treatment was carried out based on the lengths of the anatomical crowns transferred to a surgical guide that served as a reference for the incisions and also for the surgical stent for implant placement. Discussion: Crown lengthening is the procedure to treat the APE case depending on the sufficiency level of soft tissue. In this case, the treatment is complicated with implant placement and the patient's medical history and oral hygiene. Conclusion/Clinical Significance: After an excursion of treatment and 2 years of follow-up, results were favorable and dental-periodontal harmony was achieved, as well as function, aesthetics, and the patient's satisfaction. In conclusion, careful preoperative planning is required for postsurgical stability and is a crucial consideration for a successful outcome.